2022
DOI: 10.1111/exsy.12933
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Diagnosis of depression level using multimodal approaches using deep learning techniques with multiple selective features

Abstract: Depression is a serious mental health condition that may lead to poor mental and emotional functioning at work, at school and in the family causing the mental imbalance. In worst scenarios, depression may lead to severe anxiety or suicide. Hence, it is necessary to diagnose depression at early stages. This paper elaborates the development of a novel approach for a convolutional neural network model that can examine facial images from the recorded interview sessions to discover facial patterns that could indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…When measuring the efficacy of PMR combined with other interventions versus PMR as a standalone relaxation technique, there are two (2) studies in this review 66,68 that found combining PMR with other variables to be more effective compared to the PMR training alone in their respective study. Korkut, Ülker, Çidem, Şahin 66 found combining PMR with nature sound to be more effective in reducing anxiety among the nursing students, while Robb 68 highlighted that combination of PMR with music to be more effective in reducing anxiety among the university students compared to PMR alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When measuring the efficacy of PMR combined with other interventions versus PMR as a standalone relaxation technique, there are two (2) studies in this review 66,68 that found combining PMR with other variables to be more effective compared to the PMR training alone in their respective study. Korkut, Ülker, Çidem, Şahin 66 found combining PMR with nature sound to be more effective in reducing anxiety among the nursing students, while Robb 68 highlighted that combination of PMR with music to be more effective in reducing anxiety among the university students compared to PMR alone.…”
Section: Discussionmentioning
confidence: 99%
“…These poor conditions could lead to more serious psychiatric disorders or conditions such as clinical anxiety, depression, bipolar disorders, schizophrenia, or even suicide. 2–4 The aforementioned statement emphasizes the critical need to swiftly address stress, anxiety, and depression as these are major contributors to the wider range of mental health issues that people may encounter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent research gyrated around applying Machine Learning (ML) and DL methods to assess mental health indicators using actigraph measurements (Choi et al, 2021; Garcia‐Ceja, Riegler, Jakobsen, Tørresen, et al, 2018, 2020; Raihan et al, 2021; Rodríguez‐Ruiz et al, 2019, 2020; Tazawa et al, 2020). Several research (Frogner et al, 2019; Garcia‐Ceja, Riegler, Jakobsen, Torresen, et al, 2018; Jakobsen et al, 2020; Kulam, 2019; Meshram & Rambola, 2022) have been published that show how DL techniques may be used to inevitably extract features from the dataset recordings. However, the reported studies primarily focus on detection of depression as the key indicator of mental health.…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning algorithms can analyze various data sources, such as student's academic performance, participation levels, and physiological data like heart rate or skin conductance [9]. These algorithms can then identify patterns and early warning signs of anxiety [10]. Integrating active learning and machine learning techniques into the educational process makes it possible to address these indicators [11].…”
Section: Introductionmentioning
confidence: 99%